Interplay between Digital Marketing, Business Analytics and Innovation Capability: A Case of Greece SMEs - Georgia Moschogianni (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study examines the effects of digital marketing on the purchase intention and market performance of Small and Medium-Sized Enterprises (SMEs) in a developing market in Greece's pharmaceutical, IT, and service sectors. In the pharmaceutical, IT, and service industries, it also looks at how innovation capability functions as a mediating factor in the interaction between digital marketing, purchase intention, and market performance. A Partial Least Squares - Structural Equation Modelling (PLS-SEM) technique was employed to examine data from 260 Small and Medium-Sized Enterprises (SMEs) in the pharmaceutical, IT, and service industries. This study was conducted in Greece, and the targeted population was pharmaceutical, IT, and service sector owners and senior managers. As the population was unknown, it was difficult to access all the owners and senior managers from Greece's SME sector. A non-probability sampling technique was used, and the sampling method was convenient. The main objective of this paper is to identify themes and trends directly related to digital marketing, business analytics, innovation capability, and SMEs. The findings demonstrate that, through innovation capabilities in mediation, digital marketing directly impacts the market performance and purchase intention of SMEs in the pharmaceutical, IT, and service sectors. On the other hand, through the complete mediation of innovative capability, digital marketing directly influences the buying intention and market performance of SMEs in the pharmaceutical, IT, and service industries. The results of this study offer valuable insights through business, through business analytics in moderation on digital marketing and market performance and purchase intention of SMEs in the pharmaceutical, IT, and service sectors. Businesses continue to invest large sums of money in growing their Business Analytics (BA) and innovation departments, yet it is still unclear how performance is enhanced. Greece's Small and Medium-Sized Enterprises (SMEs) are an important and dynamic component of the nation's commercial environment. These businesses are essential for stimulating innovation, creating jobs, and advancing economic progress. Greece's economy is resilient and diverse because of the wide variety of SMEs that operate there in different industries. The results support earlier studies mostly carried out in developed (Western) economies. Practically speaking, this research aids SMEs in realising the value of innovation by encouraging them to test out new concepts Regularly to sustain innovation and a competitive edge in a demanding business climate. Future research directions are also given.